Impact of land-use and fecal contamination on Escherichia populations in environmental samples - Adrian L. Cookson; Jonathan C. Marshall; Patrick J. Biggs; Lynn E. Rogers; Rose M. Collis; Megan Devane; Rebecca Stott; Gale Brightwell (Scientific Reports)
Abstract Understanding the composition of complex Escherichia coli populations from the environment is necessary for identifying strategies to reduce the impacts of fecal contamination and protect public health. Metabarcoding targeting the hypervariable gene gnd was used to reveal the complex population diversity of E. coli and phenotypically indistinct Escherichia species in water, soil, sediment, aquatic biofilm, and fecal samples from native forest and pastoral sites. The resulting amplicons were cross-referenced against a database containing over 700 different partial gnd sequences from E. coli/non-E. coli Escherichia species. Alpha and beta measures of diversity of Escherichia populations were lowest in feces, soil and sediment compared to water and aquatic biofilm samples. Escherichia populations recovered from extensive freshwater catchments dominated by sheep, beef and dairy farming were extremely diverse but well-separated from a wetland dairy site. In contrast, Escherichia populations from the low-impact native forest site with fewer fecal sources were less diverse. Metabarcoding distinguished E. coli populations important to fecal contamination monitoring from non-E. coli Escherichia environmental populations. These data represent in-depth analysis and geographic stability of Escherichia populations from environmental samples with extensive heterogeneity, and reveal links with diverse fecal sources, land-use and the overall burden of fecal contamination at sample sites.